The deep intronic c.903+469T>C mutation in the MTRR gene creates an SF2/ASF binding exonic splicing enhancer, which leads to pseudoexon activation and causes the cblE type of homocystinuria - Homolová, Kateřina; Zavaďáková, Petra; Doktor, Thomas Koed; Schroeder, Lisbeth Dahl; Kožich, Viktor; Andresen, Brage S (Human mutation, 2010)
Deep intronic mutations are often ignored as possible causes of human diseases. A deep intronic mutation in the MTRR gene, c.903+469T>C, is the most frequent mutation causing the cblE type of homocystinuria. It is well known to be associated with pre-mRNA mis-splicing, resulting in pseudoexon inclusion; however, the pathological mechanism remains unknown. We used minigenes to demonstrate that this mutation is the direct cause of MTRR pseudoexon inclusion, and that the pseudoexon is normally not recognized due to a suboptimal 5' splice site. Within the pseudoexon we identified an exonic splicing enhancer (ESE), which is activated by the mutation. Cotransfection and siRNA experiments showed that pseudoexon inclusion depends on the cellular amounts of SF2/ASF and in vitro RNA-binding assays showed dramatically increased SF2/ASF binding to the mutant MTRR ESE. The mutant MTRR ESE sequence is identical to an ESE of the alternatively spliced MST1R proto-oncogene, which suggests that this ESE could be frequently involved in splicing regulation. Our study conclusively demonstrates that an intronic single nucleotide change is sufficient to cause pseudoexon activation via creation of a functional ESE, which binds a specific splicing factor. We suggest that this mechanism may cause genetic disease much more frequently than previously reported.
Keywords: mutace; Animals; Ferredoxin-NADP Reductase; Nuclear Proteins; Base Sequence; Chlorocebus aethiops; zesilovače transkripce; sestřih RNA; jaderné proteiny; RNA Splicing; introny; vazba proteinů; proteiny vázající RNA; Molecular Sequence Data; Introns; COS Cells; Enhancer Elements, Genetic; messenger RNA; Mutation; COS buňky; RNA, Messenger; RNA Splice Sites; Computational Biology; Mutant Proteins; molekulární sekvence - údaje; Exons; Vitamin B 12; mutantní proteiny; sekvence nukleotidů; RNA-Binding Proteins; ferredoxin-NADP-reduktasa; Cercopithecus aethiops; exony; Homocystinuria; zvířata; místa sestřihu RNA; výpočetní biologie; vitamin B 12; Protein Binding; homocystinurie